La efectividad de las medidas administrativas de protección de derechos emitidas por las tenencias políticas de la provincia de Chimborazo en casos de violencia contra la mujer y la familia en el período 15 de marzo del 2020 al 15 de febrero del 2022” - Avendaño Barragán, Paúl Mesías (2023)
ABSTRACT: This study addresses the basis of the identification, conceptualization and applicability of the principle of legality established in Article 14 of the Organic Administrative Code. This code relies on a fundamental right to good administration established in Article 31, which generally establishes the foundation in favor of Public Administration the discretionary power in the provision of goods and services. This applies whether this provision is through the use of public policy or the delegation of responsibilities by jurisdiction to officials representing the executive power. In this case, the study refers to the discretionary power to grant Immediate Administrative Protection Measures to Civil Authorities (Tenientes Politicos) of Chimborazo Province, who play an extremely important role in the legal and administrative organization of the state, particularly in the rural sector. These roles include maintaining administrative headquarters, granting administrative measures, prevention of violence against women, through the delegation ordered by legal mandate for the exercise of state powers established in Article 9 lit.b) of the Law to Prevent and Eradicate Violence Against Women. In view of the needs that are made visible in the course of social evolution to guarantee the suitability of special processes of a preventative and punitive nature in administrative channels, it is necessary to implement a purposeful, expeditious, functional, egalitarian, and practical justice system that guarantees the effective and appropriate execution of legal processes. The lack of implementation of Municipal Councils for the Protection of Rights in certain cases, as well as frequently populist political rather than professional appointments based on merit (knowledge, aptitudes, skills) for these positions, including the lack of academic or technical training or on-the-job training or other means of professionalization, added to social difficulties such as lack of resources and the employment of unsuitable or obsolete mechanisms for administration. This presumably means that the work of the Civil Authorities is not likely to be effective or conform to the law, making it impossible to objectively and positively attend to this type of needs, in guarantee and validity of the rights established in the Constitution that refer to the integrity of women. Furthermore, the administrative inconsistencies regarding the insufficiency of resources added to the lack of technical preparation from the legal and administrative field regarding their competences in the exercise of their functions by the Delegates of these powers probably causes the risk of promoting the practice and application of administrative legal principles and structures that positively support the applicability of the Law in its resolutions. Considering their lack of suitability, this may point to an opportunity for a technical challenge by parties due to lack of guarantees that threaten due process, for vices that affect their legality, in defense of their rights. This also contributes to serious violations of the constitutional principles regarding the fundamental rights of girls, adolescent women, young women and older adults in Chimborazo, and may be reflected in a lack of correct practice of the administrative regulations that support the matter. This can make it possible to substantiate the applicability of this research, regarding the qualitative and quantitative analysis of the public service regarding the granting of Administrative Protection Measures, through the use of methodological techniques for the development of information, in relation to its effectiveness in its current status, regarding the files belonging to the Political Holdings of the Province of Chimborazo, through the use of statistical techniques, the applicable sampling and the use of surveys, within the scope mentioned above. This thesis is based on the substantive and formal results from a study in fulfillment of a degree project based on a theoretically-based intervention proposal, a management model as a proposal for implementation, and a comparative evaluation of the effectiveness of the administrative protection measures issued by the Civil Authorities of the Province of Chimborazo, currently exercising their powers, as well as through the development of a theoretical-methodological design that analyzes and evaluates the legal, administrative and logistical structure within the scope of application, pertinent to the topic to be developed. KEYWORDS: ADMINISTRATIVE MEASURES; POLICY TENURE; EFFECTIVENESS, ENFORCEABILITY; AND, MANAGEMENT MODEL.